Cholesterol, HDL, and LDL Content in Quail Egg Yolk with Probiotics and Acidifier Feeding - Andreas Berny Yulianto; Koesnoto Supranianondo; Kartika Purnamasari (Media Kedokteran Hewan)
The higher cholesterol content in quail eggs compared to chicken and duck eggs needs to be taken into account, so there is a need for research focused on this issue. The aim of this study was to prove that the use of probiotics (Pediococcus pentosaceus ABY 118, Lactococcus lactis) and acidifiers in quail can give positive results on reducing cholesterol and LDL and increasing HDL content in egg yolk. Thirty quails were randomized into three treatments with 10 replicates. The treatments studied were: P0 = Control (no probiotic and no acidifier); P1 = Probiotic 20 ml/liter drinking water + Acidifier 5 g/kg feed; P2 = Probiotic 40 ml/liter drinking water + Acidifier 10 g/kg feed. The results of this study showed that there was a significant difference between cholesterol from the P0 with P1 and P2 treatments. Cholesterol in P1 and P2 was significantly lower than P0. HDL in the P1 and P2 treatments was significantly higher than the P0 treatment. LDL in the P1 and P2 treatments was lower than the P0 treatment. The conclusion that can be drawn from the results of this study is that the use of probiotics and acidifiers can reduce cholesterol, increase HDL, and reduce LDL.